Integrated Marketing Communications : Management of Messages to External Stakeholders - Öhman, Fredrik; Sikblad, Stina (2013)
In today's fragmented media landscape it has become increasingly important for companies to differentiate their message from all the other competitors’ messages. Another challenge for companies is to find ways to strategically communicate their corporate values, both internally and externally, so that the values are perceived unitary by companies and their stakeholders. Furthermore, it can be said that countless media options are competing for people's attention; thus it is imperative for companies´ to find optimal channels to their target audience and keep a “red thread” throughout the diversity of channels to obtain a coherent brand perception. Hence, the purpose of this study is to gain a deeper understanding of how companies can integrate their marketing communication and how they manage the communication towards the external markets (according to the concept of IMC). Furthermore, a qualitative case study with the communication bureau Yours in Luleå was conducted to reach the purpose.The findings from this thesis show that in order for companies to be successful in their external IMC, they have to identify long-term customers which in turn will ensure wealth contribution to the companies. In summary, IMC can serve as a base to help companies make the correct strategic choices and managing business processes to a high standard, which will lead to success. Validerat; 20131010 (global_studentproject_submitter)